G. Ghapantsyan as a Theorist of General Linguistics - PETROSYAN, VARDAN (Bulletin of Yerevan University B: Philology, 2021)
G. Ghapantsyan’s general linguistic viewpoints have been formulated by means of complicated reformative developments. In essence, dealing with the questions of linguistic theory, he tried to balance on the one hand the traditional linguistic directions (Young Grammarians’ doctrines, sociological doctrines, etc.) and on the other hand- the images of “new-doctrinal” linguistic ideas - taking only the most prominent concepts from these two doctrines. Of course, he did not always manage to do it, because the reality the representative of which was him was not convenient for truthful scientific values. In Armenian linguistics, it was G. Ghapantsyan, who first introduced the notions of phoneme and morpheme. With his “General Linguistics”, general linguistics was set in as a scientific discipline in Armenian linguistics.